Pengaruh Konservatisme Akuntansi dan Leverage terhadap Manajemen Laba - Tantia Rahmawati; Muhammad Aufa (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
This study aims to analyze the effect of accounting conservatism and leverage on earnings management. The population of this study are manufacturing companies in the food and beverage consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. The sample of this research is 84 samples selected based on purposive sampling technique. This study uses a quantitative method with secondary data sources in the form of a complete annual financial report of the company. The data analysis technique uses multiple linear regression analysis. The results showed that the leverage variable has a negative and significant effect on earnings management. Meanwhile, the accounting conservatism variable has no effect on earnings management.